Hydrogen/deuterium exchange mass spectrometry for characterizing phosphoenolpyruvate-induced structural transitions in Mycobacterium tuberculosis 5-enolpyruvylshikimate-3-phosphate synthase (EC 2.5.1.1) - Vaso, Alessandra [UNESP]; dos Santos, Diogenes S.; Basso, Luis Augusto; Palma, Mario Sergio [UNESP] (Elsevier B.V., 2011)
The enzyme 5-enolpyruvylshikimate-3-phosphate synthase (EPSPS) catalyzes the reaction between shikimate-3-phosphate (S3P) and phosphoenolpyruvate (PEP) to form 5-enolpyruvylshikimate-3-phosphate, an intermediate in the shikimate pathway, which leads to the biosynthesis of aromatic amino acids. The two-domain structure of EPSPS is formed by a 6-fold replication of protein folding units, each one formed by two parallel a-helices and four-stranded beta-sheets. The apo form of the enzyme exists in an open conformation, but when bound to PEP, the EPSPS conformation is closed. The H/D exchange properties of EPSPS from Mycobacterium tuberculosis (Mt) were studied for both enzyme conformations using ESI-mass spectrometry. We mapped the identified H/D exchange sites on the 3D structure. H/D exchange revealed that the enzyme undergoes extensive conformational change upon forming the PEP complex, which seem to favor solvent access at domain 1, while they partially prevent solvent access to domain 2. This may be part of the catalysis mechanism of the enzyme, stabilizing S3P binding and inducing cleft closure, which controls the entrance of substrate molecules. (C) 2010 Elsevier B.V. All rights reserved.
Keywords: ESI-MS; H/D exchange; Mass spectrometry; Proteins dynamics; Shikimate pathway